The impact of early physical rehabilitation in the intensive care unit on the mental state and cognitive functions of patients with COVID-19 - Kovalenko, Viacheslav; Kuchyn, Iurii (ScienceRise: Medical Science, 2024)
As of 2021, according to the World Health Organization (WHO), over 700 million cases of COVID-19 have been recorded globally, of which approximately 20 % required hospitalisation and 5 % were transferred to Intensive Care Units (ICU). The primary cause for hospitalisation of patients in ICU is respiratory failure caused by acute respiratory distress syndrome (ARDS) associated with COVID-19. Breathing problems, prolonged ICU stays, and the need for mechanical ventilation significantly affect patients' overall health, reducing their ability to self-care, decreasing muscle strength, and negatively impacting cognitive functions. Early physical rehabilitation is considered a potentially effective method to improve treatment outcomes, particularly in reducing anxiety and depression and restoring cognitive functions. The aim of our study is to investigate the impact of early physical rehabilitation in the ICU on cognitive function and mental state in patients with COVID-19. Materials and methods: We conducted a retrospective cohort study on patients with a confirmed diagnosis of COVID-19 who required hospitalisation in the ICU between October 2020 and March 2021. We compared the effects of one and two daily sessions of physical rehabilitation on anxiety and depression levels, as well as cognitive functions in these patients. Results: We found that two daily sessions of physical rehabilitation significantly reduced anxiety and depression levels in patients with COVID-19, especially among males. Cognitive function dynamics did not show significant differences between the groups, which may indicate the limited impact of physical rehabilitation on cognitive functions in the short term. Conclusion: Early physical rehabilitation is an important component of the treatment for patients with COVID-19 in the ICU. Increasing the frequency of physical rehabilitation sessions per day contributes to improving patients' mental state, reducing anxiety and depression, and also holds potential for preserving cognitive functions, which is critically important for the long-term recovery of patients after severe illness